Going beyond general competencies in teachers' technological knowledge: describing and assessing pre-service physics teachers' competencies regarding the use of digital data acquisition systems and their relation to general technological knowledge - Benz, Gregor; Ludwig, Tobias (Frontiers in Education, 2023)
The use of digital technologies and media in physics classrooms has pedagogical potential. In addition to everyday common technologies (e.g., presenters or computers), highly subject-specific media and technologies (e.g., simulation and digital data acquisition systems) are now available for these purposes. As the diversity of these technologies/media increases, so do the required competencies on the part of the (pre-service) physics teachers who must be able to exploit the given potential. Corresponding competency frameworks and related evaluation instruments exist to describe and assess the corresponding competencies. These frameworks and scales are characterized by their generality and do not reflect the use of highly subject-specific technologies. Thus, it is not clear how relevant they are for describing competencies in highly subject-specific technological situations, such as working with digital data acquisition systems in educational lab work settings. Against this background, two studies are presented. Study 1 identifies empirically 15 subject-specific competencies for handling digital data acquisition systems in lab work settings based on a literary review of lab manuals and thinking aloud. In Study 2, based on the 15 identified competencies, an abbreviated content- and construct-validated self-efficacy scale for handling DDASs is provided. We show that general technological-specific self-efficacy is only moderately related to the highly subject-specific self-efficacy of handling digital data acquisition systems. The results suggest that specific competency frameworks and measurement scales are needed to design and evaluate specific teaching and learning situations.